Analisis Faktor-Faktor Pemeliharaan Aset Irigasi Kabupaten Tanah Datar - Rafki, Rafki; Wardi, Wardi; Zuherna, Zuherna (Jurnal Talenta Sipil, 2024)
According to Minister of Public Works No. 12 of 2014, drainage with good conditions if drainage is able to control residential water so that it does not disturb and harm the community. However, looking at the current drainage conditions in Tanah Datar Regency, there are still many that are not well maintained. Based on field surveys, it was found that irrigation conditions in Tanah Datar district had good conditions of 56.69%, in other words, as many as 379 irrigation areas were only in good condition, the rest ± 43.31% were severely damaged and lightly damaged. This will affect planting productivity for farmers in the area around Tanah Datar Regency, (PSDA field of PUPR Office in 2023). The causes of damage to the irrigation network in Tanah Datar district in recent years are caused by landslides, overflow of irrigation water due to large amounts of sedimentation and garbage, lack of maintenance after irrigation is built, and lack of P3A members and community participation and sense of belonging to irrigation. The purpose of this study is to analyze, determine the dominant factors of irrigation asset maintenance management in Agam District and find solutions or solutions to improve the maintenance of irrigation assets in Tanah Datar District. This study used quantitative methods by distributing questionnaires to respondents. The results showed that there are 8 factors that determine the management of irrigation maintenance in Agam Regency, consisting of factors such as the physical condition of irrigation networks, planting productivity, planting facilities, personnel organization, documentation, P3A conditions, funds and community participation.